Design of an interactive web application for teaching uncertainty interpretations of clinical tests - Neher, Sebastian; Kapsner, Lorenz; Prokosch, Hans-Ulrich; Toddenroth, Dennis (Studies in Health Technology and Informatics, 2021)
Background: Assessing the uncertainty of diagnostic findings is essential for advising patients. Previous research has demonstrated the difficulty of computing the expected correctness of positive or negative results, although clinical decision support (CDS) tools promise to facilitate adequate interpretations. Objectives: To teach the potential utility of CDS tools to medical students, we designed an interactive software module that computes and visualizes relevant probabilities from typical inputs. Methods: We reviewed the literature on recommended graphical approaches and decided to support contingency tables, plain table formats, tree diagrams, and icon arrays. Results: We implemented these functions in a single-page web application, which was configured to complement our local learning management system where students also access interpretation tasks. Conclusion: Our technical choices promoted a rapid implementation. We intend to explore the utility of the tool during some upcoming courses. Future developments could also model a more complex clinical reality where the likelihood of alternative diagnoses is estimated from sets of clinical investigations.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Bayes Theorem; Clinical Decision Support; Medical Education